"The ones at the bottom of the food chain": structural drivers of unintended pregnancy and unsafe abortion amongst adolescent girls in Zambia - Joseph Mumba Zulu; Tamaryn L. Crankshaw; Ramatou Ouedraogo; Kenneth Juma; Carolien J. Aantjes (BMC, 2024)
Abstract Background Access to safe abortion care is highly unequal and fundamentally rooted in socioeconomic inequalities which are amplified by restrictive social norms and legal systems. We analyse these inequalities along the reproductive health continuum amongst adolescent girls in Zambia. Methodology This paper draws from 20 focus group discussions conducted in 2021 with community members (young/adult) in five urban, peri urban, and rural sites in Zambia. Data was analysed using thematic analysis. Results Adolescent pregnancy in the community was reported to be very common across the communities with girls from poorer families being disproportionately affected. Parents were reported to be complicit in facilitating their daughter's sexual-economic exchanges which emerged as a key driver of pregnancies. Young age and unmarried status meant adolescent girls could face triple stigma: stigma around accessing contraception to prevent a pregnancy, stigma in experiencing an unintended pregnancy and stigma around terminating an unintended pregnancy. There were clear socioeconomic differences in adolescent girl's exposure to community and health provider censure and/or acceptance of their pregnancy, and in their ability to conceal an abortion. Having the means to pay for health care allows some adolescents to seek terminations earlier and to access private health facilities while poorer adolescent girls face greater exposure to community censure through their embeddedness within the community. Abortions in this group attracts greater visibility through complications arising from their constrained choice for safe abortion methods. Stigmatising attitudes of community members also undermined adolescents' reproductive agency and mental health. For adolescents who choose to keep an unintended pregnancy, reintegration into school was highly challenging despite a national policy in place, with marriage being viewed as the only future option for poorer teenage mothers. Conclusion The embeddedness of adolescent pregnancies within community structures of economic insecurity and gendered and age-related power relations highlight the importance of introducing community level approaches to tackle unintended pregnancies and unsafe abortion. Understanding teenage pregnancy as a community issue creates opportunities for community level support to young girls especially when they return to school.